(untitled) (Publicaciones en Ciencias y Tecnología, 2007)
We show the constraints that must satisfy the N = 1 D = 4 SUGRA and the Einstein-scalar field system in order to obtain a correspondence between the equations of motion of both theories. As a consequence, we present two asymmetric BPS domain walls in SUGRA theory associated to holomorphic fake superpotentials with features that have not been reported.